The Effects of Food Labelling Information on Traditional Food Purchase Intention Among Young Adults - Aizul Azri Azizan; Nurul Shuhada Kamaluddin; Nor Qhairul Izzreen Mohd Nor; Ahmad Riduan Bahauddin (Universiti Teknologi MARA, 2024)
This study aimed to determine the acceptance of traditional food and how food labelling information could influence the purchase intention of multiple young ethnic consumers. One hundred thirty-eight respondents completed a set of questionnaires as the means for data collection in this study. The obtained data was analyzed by using descriptive analysis and the Kruskal-Wallis test. The results showed that most respondents were optimistic towards food labelling (mean=4.00±0.447). The Kruskal-Wallis test showed there were no significant differences in the attitudes toward labelling (p= 0.433, p>0.05) and purchasing intention of traditional food (p = 0.618, p>0.05) among the ethnicities. However, there is a significant difference in acceptance of traditional foods (p=0.001, p<0.005), whereas the Chinese had the lowest score. This study also showed that the labelling information could influence the consumers' purchase intention for traditional food. This study highlighted the importance of food labelling information in the traditional food industry, which can be crucial in boosting young consumers' acceptance and purchase intention.